2008
DOI: 10.1093/cvr/cvn258
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor BB stimulates vasculogenesis of embryonic stem cell-derived endothelial cells by calcium-mediated generation of reactive oxygen species

Abstract: Our data demonstrate that the pro-vasculogenic effects of PDGF-BB are mediated by Ca(2+)-induced ROS generation, resulting in the activation of an ERK1,2-mediated signal transduction cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 33 publications
5
60
1
1
Order By: Relevance
“…PI3K catalytic subunit p110a and p110 are essential for cardiovascular differentiation upon treatment of EBs with VEGF As previously described, VEGF plays a crucial role in cardiac and vascular differentiation, and acts on Flk-1 + cardiovascular progenitor cells (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009). To investigate whether PI3K class IA isoforms are essential for VEGF signaling pathways leading to cardiac and vascular differentiation of ES cells, p110a, p110b and p110 gene-inactivated EBs were treated from day 4 to day 10 of cell culture with VEGF (500 pM).…”
Section: Pharmacological Inhibition Of Pi3ks and Targeting Of Class Imentioning
confidence: 78%
See 1 more Smart Citation
“…PI3K catalytic subunit p110a and p110 are essential for cardiovascular differentiation upon treatment of EBs with VEGF As previously described, VEGF plays a crucial role in cardiac and vascular differentiation, and acts on Flk-1 + cardiovascular progenitor cells (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009). To investigate whether PI3K class IA isoforms are essential for VEGF signaling pathways leading to cardiac and vascular differentiation of ES cells, p110a, p110b and p110 gene-inactivated EBs were treated from day 4 to day 10 of cell culture with VEGF (500 pM).…”
Section: Pharmacological Inhibition Of Pi3ks and Targeting Of Class Imentioning
confidence: 78%
“…Previous studies showed that VEGF is essential for cardiomyogenesis and/or vascular differentiation (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009;Bekhite et al, 2010) and might activate PI3K (Bos 1995;Gerber et al, 1998). Moreover, it has been suggested that Flk-1 + plays a crucial role in regulating PI3K activity in endothelial cells (Gerber et al, 1998;Ferrara, 1999;Thomas and Owen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since we have previously demonstrated that NOX1 silencing by a siRNA approach could inhibit autocrine growth [9], we wanted to test the efficiency of the NADPH oxidases pharmacological inhibition in the same experimental conditions. For this purpose, we decided to use the Vasopharm BIOTECH GmbH drug VAS2870, a pharmacological NOX inhibitor, which has been useful to inhibit NADPH oxidases in preclinical assays both in vitro and in vivo [12,13].This compound showed a dosedependent inhibitory effect on cell growth in FaO cells ( Fig. 2A), which was maximal at the 25 M dose.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…These data suggest that very low but physiologically relevant concentrations of ROS may already be involved in developmental processes during organogenesis and differentiation of stem cells from the inner cell mass. The meaning of ROS during later stages of organ maturation and morphogenesis is not well defined but may at least be involved in neuronal, cardiac and vascular growth, where ROS have been shown in several studies to be involved in growth factor and cytokine-mediated signaling pathways such as the vascular endothelial growth factor/flk-1 (VEGF/flk-1) (Roy et al, 2008), platelet-derived growth factor BB (PDGF-BB) (Lange et al, 2009), cardiotrophin-1 (CT-1) (Sauer et al, 2004) and nerve growth factor (NGF)-mediated signaling pathways (Suzukawa et al, 2000). These pathways are associated to vasculogenesis, angiogenesis as well as the development of the central and peripheral nerve system, where ROS may be involved in the regulation of axon guidance through semaphorin 3A (Schwamborn et al, 2004).…”
Section: Ros Generation During Embryogenesismentioning
confidence: 99%
“…Any approaches to increase intracellular ROS, e.g. by addition of nanomolar concentrations of H 2 O 2 to differentiating embryoid bodies (Buggisch et al, 2007;Sauer et al, 1999;Sauer et al, 2000), treatment with direct current electrical fields (Sauer et al, 2005;Sauer et al, 1999;Serena et al, 2009), application of mechanical strain (Schmelter et al, 2006), treatment with cardiotrophin-1 (CT-1) (Sauer et al, 2004), PDGF-BB (Lange et al, 2009) or peroxisome proliferator-activated receptor α (PPARα) (Sharifpanah et al, 2008) resulted in prominent stimulation of cardiovascular differentiation of ES cells. Interestingly elevation of intracellular ROS by exogenous stimulators resulted in upregulation of Nox-1 and Nox-4 thus initiating a feed-forward stimulation of prolonged ROS generation (Schmelter et al, 2006;Buggisch et al, 2007).…”
Section: Ros and No In Cardiovascular Differentiation Of Es Cellsmentioning
confidence: 99%